Enhancing Nursing Students' Long-term Retention and Engagement in Medical Terminology through Mnemonic-Enhanced Multimedia Mobile Learning - Barlian Kristanto; Thanee Glomjai; Diannike Putri (Peneliti Teknologi Teknik Indonesia, 2024)
Medical terminology poses a significant learning obstacle for numerous nursing students who rely heavily on textbook definitions. However, these definitions often lack the necessary visual context to facilitate lasting comprehension. In order to enhance literacy skills crucial for safe nursing practice, it is important to explore innovative approaches. This study aimed to evaluate the effectiveness of the Picmonic application, which utilizes audiovisual narratives, in improving retention and engagement compared to traditional studying methods. A parallel group randomized controlled trial compared two learning methods among first-year nursing undergraduates at an urban university. Participants were assigned to either a textbook self-directed learning group (n=62) or an equivalent Picmonic content group (n=60), which used mnemonic visual flashcards and quizzes. Assessments were conducted at 5-, 10-, and 15-week intervals, with additional delayed testing at 1- and 3-months to examine knowledge acquisition and persistence, and to assess the effectiveness of the learning system. Students who used Picmonic had higher average test scores compared to the control group at various measurement points (p < .001). The differences in group means increased over longer intervals, suggesting that the use of multimedia in Picmonic helped with long-term recall. Picmonic users also expressed high satisfaction, voluntarily used the system, and provided positive feedback in focus groups, indicating a preference for the mnemonic-enhanced methodology (p < .001). Multimedia mnemonic educational systems, such as Picmonic, enhance medical terminology retention and engagement of nursing students compared to traditional strategies. This finding has significant implications for instructional design and clinical preparation.